The Political Law Stipulating The Age Of Marriage In Law No. 16/2019 And Its Impact On Family Harmony - ikhsan nasrulloh (UIN Siber Syekh Nurjati Cirebon, 2024)
This study aims to discover the debate regarding the age limit of marriage and the impact of early marriage on family harmony. The method used is the Normative Juridical approach. Data are obtained through literature and documentary studies and then analyzed qualitatively. The results of this study are as follows: First, the politics of law in Law No. 16 of 2019 is divided into subjective and objective dimensions. The value of justice for the age limit of marriage is realized by equalizing the minimum age of marriage of 19 years for men and women. The value of legal certainty in the regulations of Law No. 16 of 2019 has yet to be realized because there are no sanctions for violators, and there is a loophole for dispensation without clear requirements. Second, Islamic Law Review of Law No. 16 of 2019. Equality of the minimum age limit of 19 years is not contrary to Islamic law. Marriage is also considered good and safe because it has exceeded the age limit of puberty, according to the opinion of Islamic jurists. Third, the impact of underage marriage on family harmony affects the resilience of the family that is built. Economic, psychological, emotional, and mental unpreparedness. So that sustainable economic security is not achieved.